Morphology and sexual dimorphism of Acanthochelys spixii (Testudines, Chelidae) in Brazil. Issue 2 (2nd April 2016) - Bager, Alex; Lucas, Priscila Silva; Costa, Aline; Lima, Júlio Cézar Santos; Silveira, Melise Lucas
Abstract : Body size is an important parameter for ecology, reproduction, evolution, and development of animal species, besides understanding their taxonomic relationships and to establishing the relationships between individual size and shape. We evaluated the variation in body size traits, sexual dimorphism in populations of a turtle species Acanthochelys spixii across its distribution in Brazil and we described sex ratio in those populations. Description of the size-classes on these populations was also provided. We sampled 86 adults (16 in Minas Gerais (MG) and 70 in Rio Grande do Sul (RS)). The sex ratio was 1:1 in both sampling areas. Females were larger than males, and specimens from RS were larger than those from MG. The posterior-lobe width (PLW) was deemed the most significant sexing variable in a linear discriminant analysis of specimens within each state. Two variables, PLW and maximum carapace width, together distinguished the four groups (males and females in MG and RS) with 77% accuracy. Overall, most body measures were larger for both males and females in the southernmost population, inhabiting higher latitudes and lower temperatures. Regarding sexual size dimorphism, females had larger PLW than males in MG, and all variables were dimorphic in RS, in general females being larger than males.